Uso de las redes sociales por los estudiantes del subnivel de educación básica superior en las instituciones educativas fiscales y fiscomisionales de la parroquia El Sagrario de la ciudad de Loja, año lectivo 2022-2023. - Gutierrez Gutierrez, Dayanna Katherine (2023)
To date, technology energizes the teaching-learning process and among them social networks are forms of interaction or dynamic communication between people, groups, and institutions that are part of the formal and non-formal educational system, for this reason the present investigation searched determine the use of social networks by students of the upper basic education sublevel in fiscal and fiscomisional educational institutions of the El Sagrario parish in the city of Loja, school year 2022-2023. The methodology applied was the deductive method, with a quantitative approach, with a cross-sectional research design and exploratory - descriptive scope, in agreement with article 216 of the Academic Regime Regulations of the National University of Loja (2021). It was identified that students make use of social networks within the training process, they spend an average of 30 to 40 minutes a day for their studies, these are used as a means of synchronous communication between teacher-student, student-students, for answer academic questions. The characterization of social networks from their design and application allowed to know their particularities and differences, the main features in the teaching-learning process are the form of communication, collaboration through them, the creation of questionnaires, the availability of educational resources, the privacy of each social network and finally the sending and receiving of tasks. It is confirmed that social networks are used by students and there are specialized social networks for education such as Idukay and Red alumni, these are known by students as educational platforms, although their functionality is that of a social network and additionally an easily accessible tool used generally WhatsApp, Facebook. Keywords: Teaching-learning, Tics, Social networks, Higher Basic Education.